2016
DOI: 10.1007/s10802-016-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Course of Suicidal and Nonsuicidal Self-Injurious Thoughts and Behaviors in Outpatient and Inpatient Adolescents

Abstract: Suicidal and nonsuicidal self-injurious thoughts and behaviors (SITBs) among youth are major public health concerns. Although a growing body of research has focused on the complex association between nonsuicidal and suicidal self-injury, the temporal relationship between these two classes of behaviors is unclear. The current study addresses this empirical gap by examining the course of SITBs in adolescents receiving outpatient (N = 106; 82.1 % female) and inpatient (N = 174; 75.9 % female) treatment. SITBs (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 46 publications
14
96
0
3
Order By: Relevance
“…First, as documented here, the vast majority of STB emerge in adolescence prior to the typical age of college matriculation. This finding is consistent with previous research [11,12]. Thus, a shift of focus for primary prevention towards childhood-adolescence may be indicated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, as documented here, the vast majority of STB emerge in adolescence prior to the typical age of college matriculation. This finding is consistent with previous research [11,12]. Thus, a shift of focus for primary prevention towards childhood-adolescence may be indicated.…”
Section: Discussionsupporting
confidence: 93%
“…If our findings are confirmed, college students may have lower STB than adolescents aged 13–18 years [11,12], and than the general adult population aged 18–64 years [10,13]. Direct comparisons with same-aged peers not in college revealed that low college student STB prevalence may be explained, in part, by reduced matriculation among non-students who report high rates of STB during secondary school and thus, fail to matriculate into college.…”
Section: Discussionmentioning
confidence: 72%
“…A third finding from this review replicates a wellestablished trend that suicide rates are higher among older adolescents (Kõlves & De Leo, 2017;Roh et al, 2018) and young adults (Bridge et al, 2006;Cha et al, 2018) compared with younger adolescents. The age finding is also consistent with research describing the trajectories of suicidal thoughts and behaviors during adolescence, specifically that the onset of suicide ideation typically occurs during early adolescence (around ages 11-13) and, for a subgroup of youth, transitions to suicidal behavior during later adolescence (around age 15 or 16; Glenn et al, 2017;Nock et al, 2013). This previous research may suggest the existence of a developmental process (or set of processes) by which adolescents become more capable of engaging in suicidal behavior as they transition from early to later adolescence.…”
Section: (B) Malessupporting
confidence: 86%
“…However, 16.7% ( n = 13) of participants endorsed suicidality at Time 3 of the study. This increase in SI is consistent with prior literature showing a sharp increase after age 12 which cannot be fully accounted for by psychological disorders (Glenn et al, ; Nock et al, ; Nock, Holmberg, Photos, & Michel, ). Endorsement of SI prior to Time 3 was not a significant predictor in any of the models so it was dropped from final analyses.…”
Section: Methodssupporting
confidence: 92%